(untitled) (Current Horticulture, 2024)
Longmelon (Cucumis melo L. var. utilissimus), a warm season crop, can be grown in tropical and subtropical regions. The cv. AHLM 2 (Thar Sheetal) has been developed to produce early fruiting with quality fruits free from bitterness coupled with tolerance to high temperature. Varieties developed by the private sector are used by the farmers and their seed are expensive. The release of Thar Sheetal, an open-pollinated cultivar with better fruit length (27.62 cm) and fruit weight (81.82 g) is a prolific bearer (18.20-21.87 marketable fruits/ plant). Thar Sheetal has high yield potential of 136.31 q/ has under hot arid conditions, which is 22.11% higher than the control ‘Punjab Longmelon-1’. It bears tender, attractive, light green fruits which are not bitter. Thar Sheetal can withstand high temperature and is able to set fruits up to 42º C under hot arid conditions.